Cankarjevo priznanje - s poti - Lah, Klemen (Jezik in slovstvo, 2012)
The article summarises and clarifes the premises of the programme for the reform of the Cankar Award Competition that was laid out in the period 2007-2008 by a working group within the framework of the Slavic Society of Slovenia and the regional Slavic Society of Ljubljana. The reform programme was based on the comprehensive encouragement of creativity. It is therefore still topical today and could function as a stimulus for considering other organisational and content categories for the Cankar Award Competition
Keywords: Slovene; slovenščina; tekmovanja; Cankarjevo priznanje; literarni festivali; 2007-2008